Geometrical analysis of light-emitting diode for enhancing extraction efficiency - Shaari, Adam; Ahmad Noorden, Ahmad Fakhrurrazi; Mohamad, Saiful Najmee; Daud, Suzairi (Penerbit UMT, 2020)
A non-uniform current spreading in the current spreader can greatly reduce the effciency of the light-emitting diode (LED). The effects of the electrode contact area to the spreading layer towards extraction effciency of LED chips is analysed in analytical simulations. Length of current spreading and light extraction effciency is analysed for variation of contact area. The contact area value is varied by changing the shape of the electrode and the value of width of contact area. The increase in contact area decreases light extraction effciency as more light are absorbed by the bottom electrode surface. The effective current spreading length for Indium Tin Oxide (ITO) of thickness 300nm is 36.44µm. The 6 strips ‘fork’ design is the most optimum. The design has the most area for photons produced in active region to escape without reducing the area cover with current density. This enables the chip to has more extraction effciency with more uniform current spreading.